PENGELOLAAN DANA MASJID DI KOTA AMBON (Studi Terhadap Fungsi Sosial Masjid An-Nur Batu Merah dan Masjid Al-Ukhuwah Kapaha) - Rosita Tehuayo (TAHKIM, 2021)
This research aims to find out fund management of An-Nur mosque in Batu Merah village and Al-Ukhuwah Kapaha Mosque and to find out the relation of fund management of An-Nur mosque in Batu Merah village and Al-Ukhuwah Mosque in Kapaha, and social functions of both mosques. This type of research is field research with a case study approach qualitative. This research is focused on the case of "mosque fund management," as a case study using a single instrument, because it is focused on one issue and analyzed holistically. Data collection techniques such as observation, interviews, documents, and audiovisual materials. This research will reveal important data and information from mosque takmir informants, community members. The form of an interview is an open and unstructured interview. Data processing is done by checking the truth of the data, compiling the data, carrying out the coding (coding), classifying the data, correcting interview answers that are not clear. Data analysis was performed using qualitative analysis using the inductive method. The results of this study indicate that the practice of fund management at the An Nur Batu Merah Mosque and the Ukhuwah Kapaha Mosque in Ambon City still uses the old pattern, meaning infaq, almsgiving, zakat is the only source of mosque income. Management is closed and is manual. Sources of ZIS funds come from residents or worshipers and the government. While the channeling of mosque funds is intended for physical development only. This is because there is no single program launched by the management or takmir for the social benefit. The only social program carried out by the two mosques in the body service and recitation of mothers. As a result of the very low implementation of the social functions of the two mosques, it has an impact on the relationship between the management of mosque funds and the social function that is inherent as the function of the mosque in the time of the Prophet and his companions. This research has not found the relationship between fund management and mosque social functions as appropriate, as a result of the lack of social programs carried out by the An Nur Batu Merah Mosque and the Ukhuwah Kapaha Mosque in Ambon City. Keywords: Fund Management, Social Function, Mosque